Phormidium bekesiense K. Kiss - Gupta, Pratibha (Zenodo, 2021)
Phormidium bekesiense (I.Kiss) K.Kiss Preslia 73: 374 (Anagnostidis 2001). Komárek & Anagn., Cyanoprokaryota Part 2: Oscillatoriales 19 (2): 465, f. 686 (Komárek & Anagnostidis2005). — Basionym: Oscillatoria bekesiensis I.Kiss, Szegedi Pedagógiai Föiskola évkönyve 19, t. 1, f. 3-5 (Desikachary 1959). DESCRIPTION. — Trichome more or less straight or cylindrical, not constricted at the cross-walls, not attenuated towards end, capitate at the end; cells distinctly granular at the cross-walls; apical cell capitate, spherical, usually narrower than other vegetative cells (Fig. 8J). DIMENSION. — Trichome 4.6-8.5 µm broad and cells 1.6-3.5 µm long. ENVIRONMENT & HABITAT. — Freshwater species; wet rocks & in lake water; temperature 3°C. Published as part of Gupta, Pratibha, 2021, First report of diversity of Cyanobacteria of Broknes Peninsula of Larsemann Hills, East Antarctica, pp. 241-251 in Cryptogamie, Algologie 20 (15) on page 247, DOI:10.5252/cryptogamie-algologie2021v42a15, http://zenodo.org/record/7819309